Pendekatan Semiotika dalam Al-Qur’an: Menelaah Makna Simbolis dalam QS al-Fīl Perspektif Ferdinand De Saussure - An'imatul Maula, Nabila (Canonia Religia, 2024)
This study aims to analyze the symbolic meaning of QS al-Fīl uses Ferdinand de Saussure's semiotic approach, focusing on sign, signifier, and signified concepts. In QS al-Fīl, the historical narrative of the attempted destruction of the Kaaba by the army of elephants carries a symbolic dimension that illustrates God's power and the downfall of human arrogance. This qualitative study employs a library research approach and a qualitative-descriptive method. It identifies the linguistic elements in the surah as a system of signs and explores the relationship between linguistic aspects and contextual meaning. The analysis reveals that every word and phrase in QS al-Fīl contains symbols representing divine power and moral messages for humankind. In QS al-Fīl, the prominent signs include elements such as the army of elephants, the Abābīl birds, stones of burning clay, and leaves devoured by insects. Semiotic analysis suggests that these elements' signifiers (words) refer to tangible historical meanings. In contrast, the signified conveys deeper meanings, such as the manifestation of divine power, the collapse of tyranny, and the protection of the Kaaba. Furthermore, the relationship between signifier and signified in QS al-Fīl is shaped by the narrative sequence, which enhances the moral message of the surah. The study also examines the linguistic structure through the concepts of langue and parole, where classical Arabic language patterns and distinctive vocabulary are employed to depict the grandeur of the event while demonstrating the powerful use of language. Then, this study contributes to the development of a semiotic-based methodology for interpreting the Qur’an.